Strategic Decision of Product Diversification Alternatives Based On Capability: An AHP-Based Study On Bank Orange - Muhammad Habibullah Iskandar; Pri Hermawan (Program Pascasarjana STIE Amkop Makassar, 2026)
The performance of Bank Syariah in Indonesia (Bank Orange) is declining because the asset growth slows down, decreases in ROA and rosing NPF are driven by being dependent on one ultra-micro product. This paper on the other hand tests which diversification path is most aligned with a bank’s internal capabilities, recognizing that outcomes from banking diversification are equivocal and non-linear. Internal readiness is evaluated in a two-step process based on expert interviews grounded in the Resource-Based View and analysed by Thematic Analysis; The Analytic Hierarchy Process (AHP) on capabilities and diversification alternatives follows. The findings reveal Micro financing as the most aligned, Corporate financing second and low alignment for Joint financing. The research combines RBV and AHP in Sharia banking diversification, and characterizes the capability-based model as a roadmap for Bank Orange.